Bile Acids and FXR: Novel Targets for Liver Diseases - Stofan, Mary; Guo, Grace L. (Frontiers in Medicine, 2020)
Bile acids (BAs) are evolutionally conserved molecules, synthesized in the liver from cholesterol and have been shown to be essential for lipid homeostasis. BAs regulate a variety of metabolic functions via modulating nuclear and membrane receptors. Farnesoid X receptor (FXR) is the most important nuclear receptor for maintaining BA homeostasis. FXR plays a tissue-specific role in suppressing BA synthesis and promoting BA enterohepatic circulation. Disruption of FXR in mice have been implicated in liver diseases commonly occurring in humans, including cholestasis, non-alcoholic fatty liver diseases and hepatocellular carcinoma. Strategically targeting FXR activity has been rapidly used to develop novel therapies for the prevention and/or treatment of cholestasis and non-alcoholic steatohepatitis. This review provides an updated literature review on BA homeostasis and FXR modulator development.